The Correlation Between The Quality Of Mobile Dental Services And Brand Image Of Dental And Oral Hospital Jenderal Soedirman University - Prakosa, Aditya Priagung; Kumala, Lukita Intan; Mudrikah, Tania Salsa Belani; Yuristrianti, Nurrekta (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
A decline in patient visits, reduced satisfaction with hospital services, and the limited use of services by the UNSOED academic community highlight ongoing challenges in shaping the public image of RSGMP UNSOED. In response to these issues, the hospital introduced a mobile dental unit, an innovative outreach initiative that functions both as an extension of its services and as a representation of its commitment beyond the hospital walls. At the heart of building a positive image lies the quality of service delivered, which ultimately shapes how the hospital is perceived by the public. This study aimed to examine the correlation between the quality of mobile dental services and the brand image of RSGMP UNSOED. To achieve this objective, a quantitative study with a cross-sectional design and a total sampling technique was conducted involving 53 respondents who received services from the mobile dental unit between July and August 2024. Service quality was measured using the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Meanwhile, brand image was assessed through indicators of brand strength, brand favorability, and brand uniqueness. Data were collected through validated questionnaires and analyzed using chi-square tests, Fisher’s exact test, and multinomial regression. The analysis showed that all service quality dimensions had significant correlations with brand image, with p-values for tangibles (0,004), reliability (0,000), assurance (0,002), responsiveness (0,002), and empathy (0,000). Among these, empathy emerged as the most influential factor. In conclusion, there is a significant correlation between the quality of mobile dental services and the brand image of RSGMP UNSOED. Improving the quality of this service can play an essential role in strengthening the hospital’s public image.